KEDUDUKAN SURAT PESANAN DALAM PROSES JUAL BELI APARTEMEN CASA GRANDE RESIDENCE TOWER AVALON (STUDI ATAS PUTUSAN PENINJAUANKEMBALI NO. 53 PK/PDT/2021): The Position of Order Letter in The Sale and Purchase Process Of Casa Grande Residence Tower Avalon (Study Of Judicial Review Decision No. 53 PK/Pdt/2021) - Cantika, Anastasya Putri; Setiawati, Anda (AMICUS CURIAE, 2024)
The marketing of apartments with the pre-project selling system, widely used by developers, is always preceded by a purchase order letter that the signing of a PPJB will follow. In practice, the status of the purchase order letter becomes a matter of concern, whether its position is merely a memorandum of understanding (MoU) or a binding agreement that can be used as a basis for prospective buyers to demand the handover of apartment units and the implementation of AJB. One case related to the purchase order letter is the lawsuit by prospective buyers of Casa Grande Residence Apartments, who are demanding the handover of units, the issuance of SHMSRS, and the signing of AJB because they have already paid the purchase price. To determine whether the prospective buyers can assert their rights, attention must be paid to the content of the purchase order letter, whether its position is only an MoU to be followed by the signing of PPJB, or whether the purchase order letter simultaneously serves as the PPJB. It is also important to consider the customary practices in the marketing of apartments with the pre-project selling system, where the purchase order letter is simply a document containing the buyer's statement of the desired unit along with the terms and conditions set by the developer, to be followed by the signing of PPJB.